2017
DOI: 10.1002/2017jg003766
|View full text |Cite
|
Sign up to set email alerts
|

DNRA in intertidal sediments of the Yangtze Estuary

Abstract: Dissimilatory nitrate reduction to ammonium (DNRA) plays an important role in regulating the fate of reactive nitrogen in estuarine and coastal ecosystems. In this work, intertidal sediments of the Yangtze Estuary were collected in January and August 2015. Potential rates of DNRA and associated functional gene were investigated with nitrogen isotope‐tracing and molecular techniques. The measured DNRA rates ranged from 0.14 to 5.57 μmol 15N kg−1 h−1 in the intertidal sediments. DNRA rates were tightly related t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
30
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 74 publications
(33 citation statements)
references
References 73 publications
(207 reference statements)
2
30
1
Order By: Relevance
“…For this reason, DNRA may be energetically favored over denitrification in C-rich 5 anoxic environments where NO 3 − is limiting and electron donors (organic C or S -2 ) are in excess (Kraft et al, 2014;Tiedje, 1988). It has been suggested that DNRA is regulated by O 2 and is not affected by NO 2 − (van den Berg et al, 2017), which contrasts with reports of DNRA rates being stimulated by NO 2 − in estuaries (Yin et al, 2017). It is also assumed that DNRA is not affected by NH 4 + (Papaspyrou et al, 2014;Tiedje, 1988), but it has been demonstrated that NH 4 + concentration is positively correlated with DNRA rates (Lisa et al, 2015;Song et al, 2014).…”
Section: 41contrasting
confidence: 49%
See 3 more Smart Citations
“…For this reason, DNRA may be energetically favored over denitrification in C-rich 5 anoxic environments where NO 3 − is limiting and electron donors (organic C or S -2 ) are in excess (Kraft et al, 2014;Tiedje, 1988). It has been suggested that DNRA is regulated by O 2 and is not affected by NO 2 − (van den Berg et al, 2017), which contrasts with reports of DNRA rates being stimulated by NO 2 − in estuaries (Yin et al, 2017). It is also assumed that DNRA is not affected by NH 4 + (Papaspyrou et al, 2014;Tiedje, 1988), but it has been demonstrated that NH 4 + concentration is positively correlated with DNRA rates (Lisa et al, 2015;Song et al, 2014).…”
Section: 41contrasting
confidence: 49%
“…The abundance of nrfA genes is correlated with S -2 and Fe 2+ , which can enhance DNRA by providing extra free energy (Robertson et al, 2016;Yin et al, 2017). Elevated temperatures increase DNRA rates; therefore, DNRA may be an important pathway for NO 3 − conversion during summer (Yin et al, 2017).…”
Section: 41mentioning
confidence: 99%
See 2 more Smart Citations
“…ammonification, dissimilatory nitrate/nitrite reduction to ammonium, nitrate respiration, nitrogen assimilation surveys (Bu et al, 2017;Silver, Herman, & Firestone, 2001;Silver, Thompson, Reich, Ewel, & Firestone, 2005;Song, Lisa, & Tobias, 2014;Yin et al, 2017) and research with pure cultures (Bleakley & Tiedje, 1982;Mania, Heylen, Spanning, & Frostegård, 2014;Smith & Zimmerman, 1981;Stremińska, Felgate, Rowley, Richardson, & Baggs, 2012;Sun, De Vos, & Heylen, 2016) have suggested that NO 3 − -ammonifying bacteria could be a significant source of N 2 O.…”
Section: Introductionmentioning
confidence: 99%